Models of detection and layout of measuring means for transport gas monitoring system - Нефедов, Леонид Иванович; Шевченко, М.В.; Василенко, Оксана Владимировна (Eastern-European Journal of Enterprise Technologies, 2010)
In article the questions connected to singularities of gas-transport monitoring from gas-distribution points to customers are considered. It is developed mathematical and structural models for detection and layout of measuring means for gas-transport monitoring system.